Maximizing the benefits of biofilms in fermentation processes - Xu, Anming; Xin, Fengxue; Dong, Weiliang; Jiang, Min (Trends in biotechnology (Regular ed.), 2024)
Biofilm-based fermentation has great potential, as it possesses inherent characteristics such as self-immobilization, high resistance to reactants, and long-term activity. This forum focuses on research targets for promoting biofilm engineering to maximize the beneficial features of biofilms and to effectively utilize them in biofilm-mediated fermentation. Biofilm-based fermentation has great potential, as it possesses inherent characteristics such as self-immobilization, high resistance to reactants, and long-term activity. This forum focuses on research targets for promoting biofilm engineering to maximize the beneficial features of biofilms and to effectively utilize them in biofilm-mediated fermentation.